Citizenship and Minorities in Contemporary Islam (American Journal of Islam and Society, 2018)
The International Institute of Islamic Thought (IIIT) organized a panel,entitled “Citizenship and Minorities in Contemporary Islam” at the 2017American Academy of Religion (AAR) Annual Meeting. The panel washeld at the John B. Hynes Veterans Memorial Convention Center in Boston,Massachusetts on Sunday, November 19, 2017.The panel was presided by Dr. Ermin Sinanović, IIIT’s Director ofResearch and Academic Programs, and included the panelists Dr. OvamirAnjum, the Imam Khattab Endowed Chair of Islamic Studies at the Departmentof Philosophy and Religious Studies at University of Toledo; Dr.Mohammad Fadel, Associate Professor and Toronto Research Chair for theLaw and Economics of Islamic Law at the University of Toronto Faculty ofLaw; and Dr. Basma Abdelgafar, Vice President of Maqasid Institute andAssociate Professor of Public Policy ...